LA MODERNIDAD Y SUS OTROS EN AMÉRICA LATINA: VOCES Y SILENCIOS DE LA MALINCHE Y SOR JUANA INÉS DE LA CRUZ. - Sánchez, María Cecilia G. (Revista de Filosofía (00348236), 2023)
This article explores the question of the Other in Latin America, considering reflections by Levinas and Ortega y Gasset on Husserlian phenomenology. The analysis focuses on two paradigmatic figures from baroque modernity, the so-called Malinche and Sor Juana Inés de la Cruz, placed against the backdrop of the debate between Ginés de Sepúlveda and Bartolomé de las Casas in regards to the humanity or animality of indigenous peoples. Special attention is given to the perspectives adopted by Tzvetan Todorov, Leopoldo Zea, Octavio Paz, and Bolívar Echeverría on the mentioned figures.